Understanding Food Prices in Turkey: An In-Depth Interview Approach - IŞIK, Sefa; ÖZBUĞDAY, Fatih Cemil (Journal of the Human and Social Sciences Researchers, 2021)
Soaring domestic food prices, which negatively affect poverty and consumer price index, cause dissatisfaction all over the world. Turkey is one of the countries suffering from food price inflation in recent years, especially in 2018. For instance, in October 2018, food prices increased by approximately 30 percent compared to the same month of the previous year. The present study aims to determine the drivers of food prices in Turkey by using an in-depth interview approach as a qualitative method. Within the scope of this study, experts in agriculture and food sectors are interviewed, and the data obtained are interpreted with the NVivo 12 qualitative data analysis program. Based on our findings, supply-side drivers are more significant than demand-side factors in Turkey. In particular, input costs play a pivotal role in periods of depreciation of the Turkish Lira since agricultural inputs such as energy, fertilizers, animal feedingstaffs and pesticides are highly dependent on imports. Moreover, Turkey’s agricultural sector has structural problems that cannot be solved for many years. These are migration and ageing rural population, low technology and productivity, fragmented and abandoned agricultural areas, the level of education, small-scale farming, non-modern greenhouses, financing, and irrigation problems. Turkey also does not have complete and well-classified agricultural data. This is one of the main obstacles to achieving better policies for Turkish agriculture. Furthermore, it is seen that import decisions harm domestic production. Most strikingly, competition challenges and collusion-prone structures across the entire food supply chain prevent a healthy price formation. On the other hand, demand-side drivers such as export, changes in food preferences, population growth, income growth, increasing number of tourists and refugees, and food waste are also significant drivers affecting food prices in Turkey.
Keywords: 2. Zero hunger; 8. Economic growth; 1. No poverty